2010
DOI: 10.1136/hrt.2009.185595
|View full text |Cite
|
Sign up to set email alerts
|

The emerging burden of hospital admissions of adults with congenital heart disease

Abstract: The emerging burden of hospital admissions of adults with congenital heart disease Verheugt, C.L.; Uiterwaal, C.S.P.M.; van der Velde, E.T.; Meijboom, F.J.; Pieper, P.G.; Sieswerda, G.T.; Plokker, H.W.M.; Grobbee, D.E.; Mulder, B.J.M. Published in: Heart DOI:10. 1136/hrt.2009.185595 Link to publication Citation for published version (APA): Verheugt, C. L., Uiterwaal, C. S. P. M., van der Velde, E. T., Meijboom, F. J., Pieper, P. G., Sieswerda, G. T., ... Mulder, B. J. M. (2010). The emerging burden of hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(66 citation statements)
references
References 22 publications
2
59
0
3
Order By: Relevance
“…4,23,29 Young adults with CHD, on the other hand, have high health care utilization, which increases with age. 38 However, CHD is much more heterogeneous, and encompasses Ͼ100 separate conditions that require specialized medical, surgical, and imaging equipment and personnel. 12 Recent studies of the prevalence of CHD have shown that the numbers of children and adults with complex CHD is roughly equal.…”
Section: Discussionmentioning
confidence: 99%
“…4,23,29 Young adults with CHD, on the other hand, have high health care utilization, which increases with age. 38 However, CHD is much more heterogeneous, and encompasses Ͼ100 separate conditions that require specialized medical, surgical, and imaging equipment and personnel. 12 Recent studies of the prevalence of CHD have shown that the numbers of children and adults with complex CHD is roughly equal.…”
Section: Discussionmentioning
confidence: 99%
“…HCM is increasingly diagnosed in women of childbearing age due to more widespread use of echocardiography and familial screening programs. The majority of young women with heart disease, including HCM, wish to consider pregnancy and therefore obstetric admission is a common cause for hospitalisation in this patient population [1,2]. However, to date pregnancy outcome data for these patients are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging burden of hospital admissions of adults with congenital heart disease was described using a Dutch national registry. 69 During 28,990 patient-years, 2908 patients (50%) were admitted to hospital. Median age at admission was 39 years (range 18-86).…”
Section: Adult Congenital Heart Diseasementioning
confidence: 99%